Choice, Competition, and Cognition: How Arizona Charter School Leaders Interpret and Respond to Market Pressures. Issue 4 (7th August 2020) - Jabbar, Huriya; Creed, Benjamin
ABSTRACT: A key goal of school choice policies is to generate competition between schools, which should theoretically drive school leaders to improve their programs to attract and retain students. However, few studies examine how principals actually perceive and define competition. This article empirically examines school leaders' conceptions of competition and their strategic behaviors using cognitive frameworks from new institutional theory, including sensemaking theory. Drawing on data from qualitative interviews with 30 charter school leaders in Arizona, we explore how leaders' cognitive understandings of competition influence their actions in an educational "marketplace." We find charter school leaders make meaning of "competition" in different ways, influenced by their local contexts and their conceptions of what actions are legitimate. Our work suggests that it is important to study the meanings of competition to school leaders, as it has important implications for schools' competitive responses and, ultimately, student outcomes. Our work has important implications for policy makers seeking to expand school choice as it sheds light on how competition works in practice, with implications for equity and access.